Obtenção de geopolímero a partir de metacaulim ativado - Erica Antunes de Souza Vassalo (2013)
The use of supplementary cementitious materials alkali-activated has showed an economically viable alternative that greatly contributes to minimizing environmental impact. Among these materials geopolymers stand out as materials that, when in alkaline solution, harden due to polymerization. The raw material (precursory material) to produce geopolymers, are materials rich in silica and alumina. The efficiency of the activation depends on the chemical and mineralogical composition of the raw material, as well as the ratio of the molar ratios of components and curing conditions. Natural pozzolans, industrial waste, such as fly ash, metakaolin and others are commonly usea. The metakaolin, one of abundant raw materials for the manufacture of geopolymers, is a material which has potentially reactive silica and alumina ratios which vary depending on their origin. In this research a geopolymer through activation of sodium hydroxide with a metakaolin marketed in São Paulo, at room temperature and incubated at 85 ± 3°C was studied. The metakaolin was characterized by physico-chemical and mineralogical tests, using x-ray diffraction and x-ray fluorescence. The geopolymers obtained was characterized by testing thermography, infrared spectroscopy and scanning electron microscopy. The mechanical performance of geopolymers obtained was analyzed in compressive strength tests. The results allowed to know the physico-chemical and microstructural of geopolymers obtained, as well as its reaction process. Thermogravimetric analysis indicated that the polymerization reaction occurred without incubation time and that the whole process is exothermic and occurs with constant loss of mass. Through in Fourier transformed infrared spectroscopy it was possible to identify the reactive potential of the samples. The compressive strength results indicated that is necessary to maximize the resistance of these materials.